(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Modern Treatment of Chronic Heart Failure This article delves into the contemporary approaches to managing chronic heart failure (CHF), highlighting significant advancements in both medical and non-medical treatments. It covers: • Pharmacological Therapies: Key drugs such as ACE inhibitors, ARBs, beta-blockers, mineralocorticoid receptor antagonists, and SGLT2 inhibitors, which play crucial roles in improving heart function and patient outcomes. • Device-Based Therapies: Technologies like Implantable Cardioverter Defibrillators (ICDs) and Cardiac Resynchronization Therapy (CRT) devices that assist in regulating heart rhythm and improving cardiac efficiency. • Advanced Therapies: The use of Left Ventricular Assist Devices (LVADs) and heart transplantation for patients with severe heart failure, offering life-extending options. • Lifestyle Modifications: The importance of diet, exercise, patient education, and self-management in controlling symptoms and improving quality of life. • Emerging Therapies: Innovations in gene therapy, regenerative medicine, and novel pharmacological agents that hold promise for future treatments. The article underscores the multifaceted nature of CHF treatment, combining established methods with cutting-edge research to enhance patient care and outcomes.